2018
DOI: 10.3390/md16110402
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Tricycloalternarene Compounds from Endophyte Alternaria sp. W-1 Associated with Laminaria japonica

Abstract: The chemical investigation of the culture filtrate of endophyte Alternaria sp. W-1 associated with Laminaria japonica provided a new tricycloalternarene compound, 2H-(2E)-tricycloalternarene 12a (1), together with five known analogs: (2E)-tricycloalternarene 12a (2), tricycloalternarene 3a (3), tricycloalternarene F (4), 15-hydroxyl tricycloalternarene 5b (5), and ACTG-Toxin D (6). In vitro cytotoxicity against the human hepatocellular carcinoma cell line SMMC-7721 and the human gastric carcinoma cell line SGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…W-1, derived from Laminaria japonica, respectively. In the bioassay experiments, compound 317 and TCA-3a exhibited weak cytotoxicity against SMMC-7721 cells in a dose-dependent manner (IC 50 = 49.7, 45.8 µg/mL) [97]. Further studies revealed that the anticancer mechanism of TCA-3a is related to cell cycle arrest in the G1 phase, and that induction of apoptosis involved two pathways (mitochondrial and death receptor pathways) [97].…”
Section: Meroterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…W-1, derived from Laminaria japonica, respectively. In the bioassay experiments, compound 317 and TCA-3a exhibited weak cytotoxicity against SMMC-7721 cells in a dose-dependent manner (IC 50 = 49.7, 45.8 µg/mL) [97]. Further studies revealed that the anticancer mechanism of TCA-3a is related to cell cycle arrest in the G1 phase, and that induction of apoptosis involved two pathways (mitochondrial and death receptor pathways) [97].…”
Section: Meroterpenesmentioning
confidence: 99%
“…Among them, compounds 307-310 possessed a rare tetrahydrofuran ring in TCAs [80]. Two new TCA acids (tricycloalternarenes K and L) (315 and 316) [96] and a new TCA ester (2H-(2E)-tricycloalternarene 12a, 317) [97] and six known derivatives were discovered from two fungal strains, Alternaria alternata ICD5-11, associated with marine isopod Ligia exotica, and Alternaria sp. W-1, derived from Laminaria japonica, respectively.…”
Section: Meroterpenesmentioning
confidence: 99%
“…However, the entomotoxic activity of the compounds is unknown, while their cytotoxic activity has not been sufficiently studied. For instance, weak cytotoxicity of tentoxin against HepG2 [38] and HeLa cell lines [39] as well as some TCAs for various tumor cell lines [40,41] have been reported. A relationship between the production of TCAs and the cytotoxic activity of A. tenuissima MFP253011 extracts against Sf9 cells is more likely (Figure 7).…”
Section: Detection Of Entomotoxic Metabolites In a Tenuissima Extractsmentioning
confidence: 99%
“…However, entomotoxic activity of the compounds is unknown while their cytotoxic activity has not been sufficiently studied. For instance, weak cytotoxicity of tentoxin against HepG2 [38] and HeLa cell lines [39] as well as some TCAs for various tumor cell lines [40,41] was reported. Relation between the production of TCAs and cytotoxic activity of A. tenuissima MFP253011 extracts against Sf9 cells is more likely (Figure 7).…”
Section: Detection Of Entomotoxic Metabolites In a Tenuissima Extractsmentioning
confidence: 99%